2019
DOI: 10.1111/jcmm.14118
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide W regulates proliferation and differentiation of ATDC5: Possible involvement of GPR7 activation, PKA and PKC‐dependent signalling cascades

Abstract: Various neuropeptides related to the energy equilibrium affect bone growth in humans and animals. Neuropeptides W (NPW) are identical in the internal ligands of the two G‐protein receptors (GPRs) included in subtypes 7 and 8. Neuropeptides W inhibits proliferation in the cultivated rat calvarial osteoblast‐like (ROB) cells. This study examines the expression of NPW and GPR7 in murine chondrocyte and their function. An immunohistochemical analysis showed that NPW and GPR7 were expressed in the proliferative cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In contrast, after inducing the differentiation of mouse ATDC5 prechondrocytes, cells which will differentiate to proliferating chondrocytes, investigators had observed the increased expression of p21 mRNA. What's more, they noted that the expression of p21 mRNA preceded the up‐regulation of type II collagen gene(Negishi et al, 2001), an early‐chondrogenic marker(Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, after inducing the differentiation of mouse ATDC5 prechondrocytes, cells which will differentiate to proliferating chondrocytes, investigators had observed the increased expression of p21 mRNA. What's more, they noted that the expression of p21 mRNA preceded the up‐regulation of type II collagen gene(Negishi et al, 2001), an early‐chondrogenic marker(Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…2011 ). Finally, neuropeptide W can promote proliferation and differentiation in ATDC5 cells ( Wang et al . 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The intracellular signaling pathway in cardiomyocytes which is affected by the NPB and NPW remains to be elucidated. In other cell types, the NPB and NPW were shown to act via PKA and PKC signaling pathways intracellularly [ 34 , 35 ]. The effect of NPW observed in diabetic animals and not the control ones are in contradiction to the lower expression of NPWR1 in the diabetic left ventricles and suggest that NPWR1 is not the only receptor on the cardiomyocyte membrane binding NPW.…”
Section: Discussionmentioning
confidence: 99%